Alternative pre-mRNA splicing as a mechanism for terminating Toll-like Receptor signaling - Lee, Frank Fang Yao; Alper, Scott (Frontiers in Immunology, 2022)
While inflammation induced by Toll-like receptor (TLR) signaling is required to combat infection, persistent inflammation can damage host tissues and contribute to a myriad of acute and chronic inflammatory disorders. Thus, it is essential not only that TLR signaling be activated in the presence of pathogens but that TLR signaling is ultimately terminated. One mechanism that limits persistent TLR signaling is alternative pre-mRNA splicing. In addition to encoding the canonical mRNAs that produce proteins that promote inflammation, many genes in the TLR signaling pathway also encode alternative mRNAs that produce proteins that are dominant negative inhibitors of signaling. Many of these negative regulators are induced by immune challenge, so production of these alternative isoforms represents a negative feedback loop that limits persistent inflammation. While these alternative splicing events have been investigated on a gene by gene basis, there has been limited systemic analysis of this mechanism that terminates TLR signaling. Here we review what is known about the production of negatively acting alternative isoforms in the TLR signaling pathway including how these inhibitors function, how they are produced, and what role they may play in inflammatory disease.